Análisis del Modelo Z de Altman en el mercado peruano - Lizarzaburu, Edmundo R. (2014)
The research that gives rise to this article intends to provide in depth knowledge on the operation, precision, accuracy, and veracity of Altman Z-score and also to determine if it can be effective and adaptable to the conditions of a specific context such as the Peruvian market. In this vein, financial statements from 2008 and 2012 of those companies that are part of the Selective Index of the Lima Stock Exchange (isbvl) which, in the end are the most representative of the Peruvian Stock Market, are analyzed. Companies are analyzed in terms of Altman Z-score. The analysis is focused on the assessment of financial ratios which indicate the fundamental behavior of a company. It is noted that the interpretation of these ratios depends on the context and is not just numerical. It is also related to the behavior itself of the assessed company